2016
DOI: 10.1080/23322039.2016.1233628
|View full text |Cite
|
Sign up to set email alerts
|

A look at the actual cost of capital of US firms

Abstract: Abstract:The capital asset pricing model (CAPM) receives both criticism and widespread adoption by practitioners and academics as the weighted average cost of capital (WACC) equity component. This study introduces two new costs of equity measures to address CAPM criticisms and provide new perspective on WACC estimates. The firm-based measure focuses on firm-investor cash flows while the market-based measure focuses solely on actual market returns. This study applies its firm and market-based WACC measures, alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…In practice, the 10-year U.S. T-Bond yield was often chosen as the risk-free rate (Brotherson et al, 2013). However, our study employed the three-month U.S. T-Bill's secondary market rate because it was stable and consistent with the CAPM as originally derived, returns on stocks and market, and other studies (Fama and French, 1993;Harrington, 1983;Black, 1972;Kothari et al, 1995;Litzenberger and Ramaswamy, 1979;Martin and Simin, 2003;Moore, 2016;Phuoc et al, 2018;Rosenberg et al, 1985;Sharpe, 1971). The S&P 500 index was used as a proxy for the market which was consistent with other studies (Brotherson et al, 2013;Harrington, 1983;Bruner et al, 1998;MacKinlay, 1995;Rosenberg et al, 1985;Sharpe, 1971).…”
Section: Datasupporting
confidence: 63%
See 3 more Smart Citations
“…In practice, the 10-year U.S. T-Bond yield was often chosen as the risk-free rate (Brotherson et al, 2013). However, our study employed the three-month U.S. T-Bill's secondary market rate because it was stable and consistent with the CAPM as originally derived, returns on stocks and market, and other studies (Fama and French, 1993;Harrington, 1983;Black, 1972;Kothari et al, 1995;Litzenberger and Ramaswamy, 1979;Martin and Simin, 2003;Moore, 2016;Phuoc et al, 2018;Rosenberg et al, 1985;Sharpe, 1971). The S&P 500 index was used as a proxy for the market which was consistent with other studies (Brotherson et al, 2013;Harrington, 1983;Bruner et al, 1998;MacKinlay, 1995;Rosenberg et al, 1985;Sharpe, 1971).…”
Section: Datasupporting
confidence: 63%
“…Besides, this research employed the model fit using Bayesian r-squared (R2B) as suggested in other studies (e.g., Buse, 1973;Lee, 1991;Trzpiot, 2013), the absolute value of alpha since the CAPM considered non-traded factor model, and beta and its standard deviation (Beta Std) in our evaluation. The alpha and beta and beta standard deviation have been employed in other studies (e.g., Shanken, 2017, 2018;Chan and Laskonishok, 1992;French, 1992, 1993;1996a2016;Hou et al, 2015;Kozak et al, 2018;Phuoc, 2018;Phuoc et al, 2018;Stambaugh and Yuan, 2016;Trzpiot, 2013). Importantly, we employed the hypothesis/confidence interval of the interested parameter beta and the mean difference of all interested parameters using two estimators since the parameter estimates themselves did not yield enough information in decision makings.…”
Section: Evaluation Criteriamentioning
confidence: 99%
See 2 more Smart Citations
“…The short-horizon data (3-year or 3 Yr) were from May 2016 to May 2019. The risk-free rate was the three-month U.S. T-Bill's secondary market rate from the Federal Reserve Economic Data (FRED) because it was stable and employed in other studies (e.g., Fama and French, 1993 ; Kothari et al., 1995 ; Martin and Simin, 2003 ; Moore, 2016 ; Phuoc et al., 2018 ; Phuoc and Pham, 2020 ). The market was the S&P 500 index which was consistent with other studies (e.g., Brotherson et al., 2013 ; MacKinlay, 1995 ; Phuoc, 2018 ; Phuoc et al., 2018 ; Phuoc and Pham, 2020 ).…”
Section: Data Approach and Estimator And Evaluation Criteriamentioning
confidence: 99%